A techno-economic environmental cost model for Arctic shipping. (September 2021) - Joseph, Lambert; Giles, Thomas; Nishatabbas, Rehmatulla; Tristan, Smith
Highlights: A techno-economic approach is deployed to capture the complexity of Arctic voyages. Under stricter policy scenarios, operations are still viable for Handymax tankers. Under the above scenario a green ammonia/fuel cell combination is selected. Implicit damage costs must be accounted for to aid in effective policy design. Abstract: The purpose of this article is to provide a case for advancing methods in Arctic shipping towards a more complete approach. A methods assessment was used to identify core concepts in Arctic shipping and to develop a modelling approach that integrates together policy, alternative fuels, emissions and microeconomic theory - enabling the exploration of financial and implicit damage costs, opportunities and environmental risks within Arctic shipping. The integration of these paradigms can lead to more detailed insights into the economic feasibility of Arctic routes under different policy scenarios. The results indicate that by 2035 under both a business as usual and an Arctic zero emission ECA policy scenario, combined Arctic-Suez transits becomes financially viable for a Handymax wet bulker with a moderate ice class. By 2050 the transpolar route becomes accessible for 5 months for these vessels. The results also show that implicit damage costs cannot be overlooked and that it is possible to advance towards more holistic methods for assessing economic and environmental risks and opportunities in Arctic shipping. Through the incorporation of these factors, this framework can be used to assist policymakers with maximising societal welfare.